Monitoring the agri-food system in Myanmar: Rice millers – September 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of the COVID-19 crisis and political instability on Myanmar’s rice sector, we conducted a telephone survey of 388 medium- and large-scale rice millers from major rice growing regions in September 2021. This report present results from interviews conducted with rice millers from Ayeyarwady, Bago, and Yangon regions. Key findings: Banking sector disruptions remain the most significant challenge for rice millers in September 2021 (reported by 70 percent of respondents) and receiving payment for rice and making payment for paddy are among the most frequently cited disruptions. Mills are in an increasingly difficult financial situation. Working capital dropped by 24 percent compared to September last year and fewer mills sold milling byproducts–rice bran and broken rice–which are important for profitability. Overall, 68 percent of millers expect monsoon milling profits in 2021 to be less than in 2020. Lending to farmers declined in the 2021 monsoon season compared to 2020. Fewer millers offered credit to farmers and the average value of credit-out was 21 percent lower. Increased transportation costs and transportation restrictions were also widespread challenges in September 2021. Diesel prices have increased by 31 percent since December 2020 and by 10 percent since June 2021. COVID-19 safety practices jumped following Myanmar’s third wave of cases: ninety-eight percent and 97 percent of millers adopted face coverings and regular handwashing, respectively. Expected monsoon season paddy harvests and milling throughput in 2021 are lower than 2020 (55 percent and 74 percent, respectively). Mill-level rice sales prices increased between June and September, following their normal season trends. Compared to last year, milling margins were higher for Emata varieties and lower for Pawsan, but overall milling margins in 2021 have been similar to their 2020 levels. Thus, milling margins are not a major contributor to changes in retail rice prices paid by consumers this year compared to last year. Recommendations: Credit guarantees to enable banks or MFIs to expand working capital to the milling sector should be considered to ensure the financial viability of rice milling. Easing transport restrictions and re-opening export markets would bring much needed stability to rice markets while relaxing the financial and production constraints that millers are experiencing.